Risk factors for hepatitis B virus recurrence after living donor liver transplantation: A 17‐year experience at a single center. Issue 12 (24th March 2015) - Bae, Sung Kwan; Shimoda, Shinji; Ikegami, Toru; Yoshizumi, Tomoharu; Harimoto, Norifumi; Itoh, Shinji; Soejima, Yuji; Uchiyama, Hideaki; Shirabe, Ken; Maehara, Yoshihiko
Abstract : Aim: The incidence of hepatitis B virus (HBV) recurrence after liver transplantation (LT) has been reduced by prophylaxis with hepatitis B immunoglobulin (HBIG) and nucleoside analogs, but the factors associated with HBV recurrence are unclear. The aim of this study was to determine the risk factors associated with HBV recurrence after living donor LT (LDLT). Methods: A retrospective review was performed for 45 patients (28 male and 17 female; median age, 54 years) who underwent LDLT for HBV‐related liver disease and were followed up for at least 6 months between October 1996 and June 2013. The virological data, tumor burden, antiviral therapy and immunosuppressive therapy were evaluated and compared between the HBV recurrence ad non‐recurrence groups. Results: Seven of the 45 patients (15.6%) developed post‐LT HBV recurrence. The median interval between LDLT and HBV recurrence was 23.7 months (range, 0.8–35.9). Three of the seven patients (42.9%) developed recurrence after cessation of HBIG, and three (42.9%) were cases with hepatocellular carcinoma (HCC) recurrence after LDLT. The remaining case underwent transplantation from a donor with positive hepatitis B surface antigen. Based on the univariate and multivariate analyses, HBIG cessation (hazard ratio [HR], 20.17; 95% confidence interval [95% CI], 2.091–194.593; P  = 0.009) and HCC recurrence (HR, 30.835; 95% CI, 3.132–303.593; P  = 0.003) were independent risk factors for HBV recurrence after LDLT. Conclusion: In LDLT patients, cessation of HBIG and HCC recurrence were risk factors associated with HBV recurrence, so careful monitoring for serological HBV markers is needed in patients with these factors.